Rainwater harvesting: harnessing traditional approach to reduce flash floods in Ibadan metropolis (2013)
This paper presents an empirical case study of domestic rainwater harvesting (RWH) techniques that could be employed to reduce surface run-off Equations were derived to calculate the potential amount of rainwater that could be harvested and the actual amount of rainwater harvested by 178 buildings with rainwater harvesting facilities at Coca-Cola Area on 26 August, 2011 when lbadan metropolis was devastated by flash flood. The study found that, through rooftop catchment techniques, as much as 90 per cent of runoff water could be harvested and that 100 per cent is achievable if augmented with surface catchment techniques for open spaces within the metropolis. The paper concludes that incorporating indigenous and modern rainwater harvesting techniques into the management of flood in Ibadan metropolis will not only mitigate the risks associated with flood, but will also enable sustainable access to domestic water and promote urban agriculture and household food security